ALD coating of centrifugally spun polymeric fibers and postannealing: case study for nanotubular TiO2 photocatalyst. Issue 15 (14th July 2021) - Rihova, Martina; Yurkevich, Oksana; Motola, Martin; Hromadko, Ludek; Spotz, Zdenek; Zazpe, Raul; Knez, Mato; Macak, Jan M.
Abstract : Proof-of-concept work on ALD coating of polymeric fibers and post-annealing leading to novel nanotubular structures: case study for TiO2 nanotubes. Abstract : This work describes the synthesis of highly photocatalytically active TiO2 tubes (TiTBs) by combining centrifugal spinning and atomic layer deposition (ALD). Poly(vinyl pyrrolidone) (PVP) fibers were first produced by centrifugal spinning and subsequently coated with TiO2 with various film thicknesses in a fluidized bed ALD reactor. After annealing of the TiO2 ALD coated PVP fibers, TiO2 tubes (TiTBs) with excellent textural properties and diameters in the range from approx. 170 to 430 nm were obtained. The morphology and structure of all TiTBs were investigated by scanning and transmission electron microscopy (SEM and TEM), X-ray diffraction (XRD), and Brunauer–Emmett–Teller analysis (BET). Liquid phase photocatalysis was conducted to determine the photocatalytic activity of the TiTBs. The photocatalytic activity of the TiTBs obtained after 50 TiO2 ALD cycles (degradation rate 0.123 min −1 ) was twice that of the reference TiO2 P25. The underlying reasons for the remarkable photocatalytic performance were textural properties of the resulting tubes along with suitable crystallinity, embedded within the 1D tubular morphology. The herein presented proof-of-concept approach paves a way for the processing of various polymeric fibers into various tubular nanostructures.